1993
DOI: 10.1143/jjap.32.4674
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Study of Centers Formed in γ-Irradiated PbCl2 Crystals

Abstract: An analisis is presented by utilizing the electron spin resonance spectra of new defects which are produced in PbCl2 single crystals irradiated at liquid nitrogen temperatures with γ-rays from a 60Co source. One of the g tensor axes of the defects corresponds to the crystallographic c-axis, and the other two make an angle of about 12° with the a- and b-axes. The components of the g-factor are g x =1.494±0.005, g y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…IV A. A similar rotation-angle dependence of the STEL in PbCl 2 shows the twofold splits when the B is in the bc and the ac planes; 14,15 the splits come from the two configurations reflecting the crystallographic symmetry. However, the explicit split has not been observed in TL was observed over 90-140 K, strongly in 100-105 K. The TL spectrum measured around the peak of the TL curve is displayed in the inset of Fig.…”
Section: A Properties Of Esr Spectramentioning
confidence: 73%
“…IV A. A similar rotation-angle dependence of the STEL in PbCl 2 shows the twofold splits when the B is in the bc and the ac planes; 14,15 the splits come from the two configurations reflecting the crystallographic symmetry. However, the explicit split has not been observed in TL was observed over 90-140 K, strongly in 100-105 K. The TL spectrum measured around the peak of the TL curve is displayed in the inset of Fig.…”
Section: A Properties Of Esr Spectramentioning
confidence: 73%
“…3, which was measured like curve (a), shows the STH centers of Pb 3+ in PbCl 2 . Though the STEL centers of Pb 2 3+ in PbCl 2 were first observed after x-or γ-ray irradiation at 80 K [14,15], the STEL centers are not detected at 0-1700 mT after photoirradiation below 50 K as shown in Fig. 3(b); indeed, the STEL centers of Pb 2 3+ appears thermally above 60 K [7].…”
Section: Experimental Results: Lead Bromide and Lead Chloridementioning
confidence: 92%
“…3(b); indeed, the STEL centers of Pb 2 3+ appears thermally above 60 K [7]. If electrons below 50 K do form self-trapping centers of Pb + or Pb 2 3+ , they could be detected in the range of 0-1700 mT because they usually have g values of 1-1.6 [14,15,16]. However, since they are not observed, other electron-trapping centers associated with lattice defects are most likely below 50 K.…”
Section: Experimental Results: Lead Bromide and Lead Chloridementioning
confidence: 99%
“…The nature of the luminescence center responsible for the BG band has not yet been made clear. From electron spin resonance (ESR) experiments, 9,10) it was found that an electron is self-trapped at a pair of nearest neighbor Pb 2þ ions along the a axis of the PbCl 2 lattice. Nistor et al 11) reported that the self-trapped electron (STEL) center described as a Pb 3þ 2 ion can be produced by UV light illumination in the region above the band gap.…”
Section: X1 Introductionmentioning
confidence: 99%